2001
DOI: 10.1007/s007840100119
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of cast-gold inlays in a specialized dental practice

Abstract: At a dental office in Münster, Germany, the majority of gold inlays incorporated between July 1969 and August 1999 (n=2,071) in 531 patients were checked with reference to the dental records and assessed retrospectively to determine their longevity. One hundred seventy-five gold inlays were rated as failures (no longer in situ); 10 abutment teeth were extracted. The 20-year Kaplan-Meier survival rate for restoration-bearing teeth was 98.9%, and the 25-year rate for all gold inlays 73.4% (+/- 4.0%; 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
1
16
0
2
Order By: Relevance
“…Erpenstein and others evaluated 2,071 gold inlays over a period of up to 30 years and found a survival rate of 97% after 10 years and 73% after 25 years. 12 Reiss and others obtained similar results in their long-term study with CAD/CAM-manufactured ceramic inlays. 29 After 10 years of wear, 90% of the restorations were assessed as a clinical success.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Erpenstein and others evaluated 2,071 gold inlays over a period of up to 30 years and found a survival rate of 97% after 10 years and 73% after 25 years. 12 Reiss and others obtained similar results in their long-term study with CAD/CAM-manufactured ceramic inlays. 29 After 10 years of wear, 90% of the restorations were assessed as a clinical success.…”
Section: Discussionsupporting
confidence: 57%
“…[1][2][3][4][5][6][7][8][9][10][11] However, long-term studies are needed to compare the clinical behavior of the different materials for posterior restorations. [12][13][14][15][16][17][18][19][20][21][22][23] The clinical performance of several esthetic tooth-colored materials has been analyzed in various studies. Frankenberger and others evaluated IPS Empress inlays and onlays over a period of six years.…”
Section: Introductionmentioning
confidence: 99%
“…After an observation period of 25 years, 2,071 restorations were included in the analysis. 13 In a two-year prospective study, Federlin and others found no difference in failure rate between partial gold crowns and partial ceramic crowns. 14 Stoll and others examined 3,518 cast gold restorations that were placed by students and postgraduate dentists at a dental school.…”
Section: Discussionmentioning
confidence: 94%
“…The survival rate following a specific number of years is frequently presented as a statistical quantity, for instance, the five-year survival rate. 20,21 However, stating the survival rate in terms of a fixed number of years also implies that information resulting from cases beyond this limit is not taken into consideration. 19,22 To avoid this disadvantage, the method of actuarial life table analysis has found widespread use in medical studies, in particular studies of cancer treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the Kaplan-Meier method is regarded as being able to deliver more accurate estimates for the survival probability than the actuarial life table method 24 and is applied in numerous dental restoration studies. [8][9][10][11][16][17][18]20,21,25,26 Especially in large treatment centers, there are two reasons that the retrospective evaluation of patients' cards presents the risk of overlooking a substantial portion of interesting cases. For one thing, it can be difficult to recover all interesting cases and for another, the patients' cards may, for whatever reasons, be unavailable at the time of evaluation.…”
Section: Discussionmentioning
confidence: 99%